2023
DOI: 10.51620/0869-2084-2022-67-6-330-333
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Zinc Level With Pathogenetically Significant Homeostasis Disorders in Severely Burned Patients

Abstract: The aim of the study was to assess the zinc content and identify the relationship between the concentration of this element and changes in the biochemical status of patients and markers of inflammation during burn shock. We examined 23 patients aged 45.3±16.1 years with burns of I-II-III degree, area of 31-80%. The serum concentrations of zinc, albumin, interleukin-6, C-reactive protein (CRP), alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were determined. The majority of patients (21/23) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Besides, no significant relationship was observed between iron, zinc, selenium, T3, TSH, and the length of stay in the ICU, and there was a significant relationship only for T4. The study by Kostina et al also showed that the decrease in serum zinc level continues until the days after the burn (23). These results were in line with the 2022 study in which mineral salts of 62 burn patients were examined for 8 days after the burn.…”
Section: Discussionsupporting
confidence: 63%
“…Besides, no significant relationship was observed between iron, zinc, selenium, T3, TSH, and the length of stay in the ICU, and there was a significant relationship only for T4. The study by Kostina et al also showed that the decrease in serum zinc level continues until the days after the burn (23). These results were in line with the 2022 study in which mineral salts of 62 burn patients were examined for 8 days after the burn.…”
Section: Discussionsupporting
confidence: 63%
“…Both our results and the literature data indicate that the inflammatory state, with the onset of hypercatabolism, hypermetabolism and fluid shifts, is accompanied by a decrease in the concentrations of negative acute-phase proteins, such as albumin and prealbumin, while positive acute-phase proteins, like CRP, rapidly increase. Considering zinc binding to cellular proteins, its serum levels will continue to decline as long as the inflammatory state is present [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%